1991
DOI: 10.1111/j.1651-2227.1991.tb11726.x
|View full text |Cite
|
Sign up to set email alerts
|

Intact Parathyroid Hormone Levels during Pregnancy, in Healthy Term Neonates and in Hypocalcemic Preterm Infants

Abstract: We measured parathyroid hormone levels in pregnant and nonpregnant women and at 1, 2 and 5 days of life in healthy term neonates and in hypocalcemic preterm infants using a new immunoradiometric assay which measures only biologically active intact parathyroid hormone and by a mid-molecule parathyroid hormone radioimmunoassay. During pregnancy intact and mid-molecule parathyroid hormone levels did not show any modification and were not different from parathyroid hormone levels of nonpregnant age-matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…Serum phosphorus shows no change in most studies during human pregnancy (33,207,221,294,468,632,641,674,791) and was similarly unchanged during twin pregnancies (646). There is also no change in the renal tubular reabsorption of phosphorus (207,329,468).…”
Section: Calcium and Phosphorusmentioning
confidence: 86%
See 2 more Smart Citations
“…Serum phosphorus shows no change in most studies during human pregnancy (33,207,221,294,468,632,641,674,791) and was similarly unchanged during twin pregnancies (646). There is also no change in the renal tubular reabsorption of phosphorus (207,329,468).…”
Section: Calcium and Phosphorusmentioning
confidence: 86%
“…Later innovations resulted in the ability to measure the ionized calcium with ion-specific electrodes. Both cross-sectional (210,227,324) and longitudinal studies (221,294,721,739,791,809,813) have shown that the ionized calcium does not change during human pregnancy, even though the mean serum calcium simultaneously drops ϳ10% into the hypocalcemic range (221).…”
Section: Calcium and Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation
“…In human babies, PTH also circulates at low levels compared with the maternal circulation and normal adult values; very low (Ͻ0.5 pM) concentrations may be observed (20, 143, 168, 177, 255, 306, 501, 544, 571, 580, 598 -600, 671, 736). This suppression of PTH has been observed as early as 19 wk of gestation in preterm babies (501,571,580,599), although one study found unsuppressed PTH values in cord blood of infants aged 31-36 wk (152). The suppression of fetal PTH is considerable when it is realized that the maternal PTH value is also usually suppressed during pregnancy compared with normal adult values, at least in women from North America and Europe (328,339).…”
Section: Pthmentioning
confidence: 99%
“…Subsequent studies used intact PTH assays but obtained measurements solely at birth and 24 h later, and demonstrated that PTH rose significantly (31,386,388,416,444,473,580). Those studies did not determine when the PTH value increased or whether the peak level was achieved at 24 h or later.…”
Section: Human Datamentioning
confidence: 99%